2003
DOI: 10.2337/diacare.26.1.168
|View full text |Cite|
|
Sign up to set email alerts
|

l-Arginine: An Ultradian-Regulated Substrate Coupled With Insulin Oscillations in Healthy Volunteers

Abstract: OBJECTIVE -Coupled oscillations of 50 -110 min in insulin and glucose have been found previously in healthy men under continuous enteral nutrition. Because L-arginine induces insulin release as glucose does, we tested the hypothesis that L-arginine can also display such an ultradian rhythm.RESEARCH DESIGN AND METHODS -Seven healthy male subjects participated in one experimental night during which blood was sampled every 10 min from 2300 to 0700. Plasma glucose, C-peptide, and L-arginine levels were measured si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Ornithine (and arginine, although not deemed ultradian in this study) are directly implicated in the latter steps of the urea cycle, suggesting ultradian rhythms in liver urea formation. While our observations are made in the vole, arginine blood concentrations have also been shown to exhibit ultradian rhythms in healthy human male volunteers, and have been linked to insulin‐mediated glucose homeostasis 52 . Indeed, both insulin and glucose have been shown to exhibit an ultradian pattern in blood concentrations in humans that persists during constant enteral nutrition 53,54 confirming intrinsic, non‐food‐driven ultradian rhythms in glucose homeostasis.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Ornithine (and arginine, although not deemed ultradian in this study) are directly implicated in the latter steps of the urea cycle, suggesting ultradian rhythms in liver urea formation. While our observations are made in the vole, arginine blood concentrations have also been shown to exhibit ultradian rhythms in healthy human male volunteers, and have been linked to insulin‐mediated glucose homeostasis 52 . Indeed, both insulin and glucose have been shown to exhibit an ultradian pattern in blood concentrations in humans that persists during constant enteral nutrition 53,54 confirming intrinsic, non‐food‐driven ultradian rhythms in glucose homeostasis.…”
Section: Discussionmentioning
confidence: 57%
“…While our observations are made in the vole, arginine blood concentrations have also been shown to exhibit ultradian rhythms in healthy human male volunteers, and have been linked to insulin-mediated glucose homeostasis. 52 Indeed, both insulin and glucose have been shown to exhibit an ultradian pattern in blood concentrations in humans that persists during constant enteral nutrition 53,54 confirming intrinsic, non-food-driven ultradian rhythms in glucose homeostasis. Recently it has been suggested that other amino acids such as leucine and glutamine may be modulators of pancreatic insulin secretion, 55 and both amino acids exhibit ultradian rhythmicity in our current metabolomics analysis.…”
Section: Ultradian Metabolic Rhythms With ~3 To 4 H Periods Do Not Ma...mentioning
confidence: 98%
“…6-24 M 7-14, Adult or NA NA Goji, 1993;Kimura and Tsai, 1984;Minamitani et al, 1989;Mitsugi and Kimura, 1986;Tannenbaum and Ling, 1984;Tannenbaum and Martin, 1976;Yonezawa et al, Brandenberger et al, 1987;Lefcourt et al, 1999;Polonsky et al, 1988;Schaefer et al, 2003;Scheen et al, 1996;Shapiro et al, 1988;Simon and Brandenberger, 2002;Simon et al, 1987;Sturis et al, 1992 GBA Ghrelin Bagnasco et al, 2002a;Mingrone et al, 2006;Tolle et al, 2002 GBA Bagnasco et al, 2002a;Licinio et al, 1997Licinio et al, , 1998aLicinio et al, , 1998bSaad et al, 1998;…”
Section: -20mentioning
confidence: 99%
“…In addition, 2-to 8-h URs in intestinal activity (Ariga et al, 2007;Code and Marlett, 1975;Deloose et al, 2012Deloose et al, , 2015Fujino et al, 2003;Hoogerwerf, 2010;Husebye et al, 1990;Masuda et al, 2000;Zheng et al, 2009) can be initiated by administration of ghrelin or the related peptide motilin. In rats, plasma ghrelin and leptin and, in humans, glucose and insulin URs occur both in fed and fasted conditions (Bagnasco et al, 2002b;Schaefer et al, 2003;Scheen et al, 1996;Shapiro et al, 1988;Simon et al, 1987;Simon et al, 1998;Simon and Brandenberger, 2002;Sturis et al, 1992), suggesting that these rhythms are not only food entrained but also endogenously maintained. Although interindividual variability makes clear that multiple stable states of varying periodicity exist, the periodicities and phase alignments of GBA components provide compelling evidence for a temporally organized GBA network structure on an ultradian timescale.…”
Section: -20mentioning
confidence: 99%
“…One putative mechanism is the formation of nitric oxide (NO) from l-arginine by NO synthase in pancreatic β cells. 10 Arginine is required for the production of NO via catalysis to citrulline by NO synthase (NOS), 11 and the prevailing hypothesis is that greater arginine bioavailability may stimulate NO production and insulin sensitivity 12,13 ; thus, disturbances in the arginine-NO pathway may underlie both CVD and T2D pathogenesis through similar mechanisms, such as chronic inflammation, mitochondrial dysfunction and oxidative stress. [14][15][16] Nevertheless, a potential role for arginine in the primary prevention of diabetes is still debated.…”
Section: Discussionmentioning
confidence: 99%